Understanding Zalora's Neuromarketing-Based Online Marketplace Customer Choices - Rizal, Saepul; Pasaribu, Popy Novita; Sutisna, Nandang (INOVATOR, 2023)
The development of the internet has popularized Digital commerce (e-commerce). There are various types online marketplaces with unique customer bases. Customers develop preferences or choices for certain online marketplaces over competitors. This research is to find out the choice variables that can influence. This study looks at online parameters that affect user experience when shopping. Included in this research are the discoveries of neuroscience, a type of limbic system that is basically similar to a client's personality. Descriptive analysis was used to analyze the customer's limbic personality, and regression analysis using the SPSS application was used for online shopping attitudes. The research subject is an online shop with Zalora marketplace. The author uses the snowball method to collect data into Google Forms. The total of all respondents is 36 people. Zalora types of emotional types found as joy and pleasure. Zalora Limbic Map is a fantasy/entertainment system for balance. The most important aspects of brand identity are interaction, quality of information, usability, entertainment and personalization of customer preferences when shopping with Zalora. The SPSS partial test results show that the personalization variable significantly influences Zalora's marketplace preferences. In addition, the usability variable and the domain name affect it negatively, although not significantly. The model can explain consumer preferences for the Zalora marketplace by 63.7%.